Photo-Degradation of Phenol Using TiO2/CMK-3 Photo-Catalyst Under Medium Pressure UV Lamp - Alireza Rahmani; Hadi Rahimzadeh; Somayeh Beirami (Hamadan University of Medical Sciences, 2018)
Phenol is considered as one of the major environmental concerns due to its characteristics including chronic toxicity, biological stability, and increasing the toxicological intermediates after biological degradation. Therefore, the aim of this study was to evaluate the photo-degradation of phenol using the titanium dioxide (TiO2) photo-catalyst on ordered mesoporous carbon (CMK-3) support under UV irradiation. In this study, the effects of some parameters including pH value (4, 5, 6, 7, 8, 9, 10), TiO2/CMK-3 concentration (0.05, 0.1, 0.15, 0.3, 0.5 g/L), irradiation time (30, 60, 90, 120, 150 min), and phenol concentration (50, 100, 150 and 200 mg/L) were assessed. The properties of the CMK-3 and TiO2/CMK-3 were compared using the transmission electron microscopy (TEM), X-ray powder diffraction (XRD) and N2 adsorption-desorption isotherm. The results revealed that the process studied was remarkably affected by the parameters, and the optimum values of the parameters were as follows: pH=6, TiO2/CMK-3 concentration =0.15 g/L, phenol concentration = 100 mg/L, and irradiation time=150 min. The phenol degradation efficiency and total organic carbon (TOC) removal efficiency for phenol were 96% and 74%, respectively. Moreover, the stability greater than 7 times for the studied photo-catalyst was indicative of its high potential to be used in photo-degradation processes for the elimination of pollutants.